Desenvolvimento e fisiologia de enxertos do tomateiro ‘Santa Clara’ em função de porta-enxertos e infestação com o falso nematoide das galhas - Garita, Sebastián Andrés (2015)
Nacobbus aberrans, known as the 'false nematodes root-knot' is a sedentary endoparasitic pathogen that causes serious economic losses in the tomato production. The use of resistant rootstocks to control soil-borne pathogens is a practice that has good potential for application, since they have no negative environmental effect and does not require the producer to modify his usual practices. Several rootstocks were evaluated and listed as resistant to many soilborne pathogens, but none of them was resistant to N.aberrans. During the research carried out for this study two rootstocks Solanum lycopersicum L. var. cerasiforme 'Carolina' and S. lycopersicum L. 'Maxifort', were evaluated, being S. lycopersicum L. 'Santa Clara' grafted onto both of them. In addition, some ungrafted Santa Clara plants were used as a control to carry out a comparison with the grafted ones. The grafted and the ungrafted plants were grown on two kinds of substrate with and without the N aberrans. Were evaluated Growth parameters (height, shoot dry weight, fresh weight of root and stem diameter); Physiological indicators of stress (proline and malondialdehído concentrations and electrical conductivity relative); and the pathogen’s factor of reproduction. The plants grafted on 'Maxifort showed similar growth to the ungrafted plants, and the grafts grown upon 'Carolina' had lower height than the other plants. In the presence of the pathogen, the growth parameters tended to decrease, being that in some cases the values of such reduction were significant. The parasitism caused changes in the metabolism of plants. This assertion can be confirmed by the stress indicators. Reproductive factors were 3.68; 5.47 and 2.76 for non-grafted, 'Carolina' and 'Maxifort', respectively, and according with Oostenbrink can be classified as susceptible. However, if the Hadisoeganda and Sasser (1982) calculation was taken as classification criteria, the 'Maxifort' would be classified as moderately resistant, and the "Carolina" and "Santa Clara" as susceptible. Thus, the selection of a rootstock must be the result of a joint assessment of growth factors, productivity and stress tolerance, since the use of a single deciding factor may lead to make the wrong choice of cultivar or variety, used either as rootstock or as an ungrafted plant.